Enhancement of Knowledge and Training for Independent Physiotherapy Management of Low Back Pain by Physical Activity Using Pamphlet Media at Posbindu, Candisari Village, Banyuurip, Purworejo - Husna Arwa Salsabil; Herta Meisatama; Nurul Rachmah Alia Fitri (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The community in the village is often involved in agricultural or household work that requires heavy physical activity, but they often lack knowledge or access to healthcare, including physiotherapy, to address back pain. The training, in the form of simulations, provided practical skills on how to perform self-exercises at home. The purpose of this activity was to increase the knowledge of the community in Candisari Village, Banyuurip, Purworejo, about physiotherapy and techniques for independently managing back pain, using pamphlets at Posbindu as an effective way to convey information to the rural community. The results showed an average pretest score of 66.9 points, while the average posttest score was 80.7 points. The difference between the pretest and posttest scores indicated an increase of 13.8 points, demonstrating an improvement in the knowledge of the Candisari Village community, Banyuurip, Purworejo, about independent physiotherapy training for managing back pain due to intense physical activity using pamphlets.